Development of Digital Registration Information System in Kelurahan to Improve Administration Efficiency and Transparency - Putri, Riski Ananda (SAN Scientific, 2024)
This research aims to develop a digital registration information system in urban villages to increase efficiency and transparency in administrative processes. This web-based designed information system is expected to be able to overcome various problems that often occur in manual administration, such as data inaccuracies, long processing times, and lack of transparency. The research methods used include literature study, needs analysis, system design, implementation, and evaluation. At the initial stage, a needs analysis is carried out to identify the features needed by users, namely village staff and residents.The results of this analysis are used as a basis in designing system architecture and user interfaces. System implementation is done using the latest web technology that ensures the system can be accessed easily and securely. Next, the system is tested through several stages of trials involving end users to ensure its functionality and reliability.The results showed that this digital registration information system was able to increase the efficiency of the administrative processby up to 40% compared to the manual method, as well as increase transparency through real-time application status tracking features and structured data storage. With this system, residents can register and monitor the status of their applications online, reducing the need to come directly to the village office. The conclusion of this study is that the development of a digital registration information system in urban villages can significantly improve administrative efficiency and transparency, as well as provide convenience for residents in accessing public services. It is expected that this system can be widely implemented in various urban villages to support the modernization of public services in Indonesia.